Hand Fatigue Analysis Using Quantitative Evaluation of Variability in Drawing Patterns - mohamadali Sanjari; farzaneh , Haghighat; gholamreza Olyaee; aliashraf Jamshidi (Armaghane Danesh Bimonthly Journal, 2015)
Background & aim: Muscle fatigue is defined as the reduced power generation capacity of a muscle or muscle group after activity which can lead to a variety of lesions. The purpose of the present study was to define the fatigue analysis by quantitative analysis using drawing patterns.